4g+g-3G-g=16

Simple and best practice solution for 4g+g-3G-g=16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4g+g-3G-g=16 equation:


Simplifying
4g + g + -3G + -1g = 16

Reorder the terms:
-3G + 4g + g + -1g = 16

Combine like terms: 4g + g = 5g
-3G + 5g + -1g = 16

Combine like terms: 5g + -1g = 4g
-3G + 4g = 16

Solving
-3G + 4g = 16

Solving for variable 'G'.

Move all terms containing G to the left, all other terms to the right.

Add '-4g' to each side of the equation.
-3G + 4g + -4g = 16 + -4g

Combine like terms: 4g + -4g = 0
-3G + 0 = 16 + -4g
-3G = 16 + -4g

Divide each side by '-3'.
G = -5.333333333 + 1.333333333g

Simplifying
G = -5.333333333 + 1.333333333g

See similar equations:

| -7(7+4x)=-273 | | 3t+6t-8t-1=13 | | 15q-3q-19q-2q+q-1=2 | | -4(-5-6x)=236 | | 4x+22=7x-50 | | -5(8+2n)=-220 | | 2x^2+7xy+7y^2+18y-8=0 | | 35=1/2(7)(x) | | 4v-v+2v-3v=18 | | 7(-2+3x)=112 | | -16x-14=-94 | | 13x-11-20x=17 | | 65=4u-11 | | 2q-q-1=12 | | 35=1/2•7•x | | 14b-6b=16 | | 7(2x+6)=42 | | 4y-10=42 | | 2x^2-y^2-10x+3y-11=0 | | 16k+6k-19k=18 | | -3=-4(-9)+1 | | 90000000000000000000000000000000000000000000000000000000000000000000000=8x | | 2x^2+10x+3y-11=0 | | -195+9x+12x=57 | | B-12=18 | | 9=b-7 | | 2x-1=-2x+15 | | 500000000000000000000000000000000000000x=777777777777777777 | | X/9=15/6 | | 20b-7b-16b=18 | | 5+t=10t-7 | | 66=3v+12 |

Equations solver categories